Skills beyond school : synthesis report - (:unkn) unknown (OECD Publishing, 2014)
"School and university, and the well-trod path between them, play a dominant role in thinking about education policy. But outside these two institutions there exists a less well understood world of colleges, diplomas, certificates and professional examinations - the world of post-secondary vocational education and training. Many professional and technical jobs require no more than one or two years of career preparation beyond upper secondary level, and in some countries as much as one-quarter of the adult workforce have this type of qualification (see ). Nearly two-thirds of overall employment growth in the European Union (EU25) is forecast to be in the 'technicians and associate professionals' category - the category most closely linked to this sector. A recent US projection is that nearly one-third of job vacancies by 2018 will require some post-secondary qualification but less than a four-year degree. The aim of this OECD study is to cast light on this world, as it is large, dynamic, and of key importance to country skill systems." (Editor, BIBB-Doku)
Dt. Ausgabe u.d.T.: Postsekundäre Berufsbildung
Keywords: S 2.3 Berufsbildungspolitik; I 2.2 Europa; Berufsbildungssystem; Berufsbildungspolitik; Höhere Berufsbildung; Hochschulzugang; Internationaler Vergleich; Europa; Österreich; Schweiz; Bundesrepublik Deutschland